Erotica as Public Pedagogy: Learning Identity through Popular Cultural Sources - Carolyn Meeker; Craig M. McGill (Adult Education Research Conference, 2019)
Women who are feminist and submissive struggle to learn about and navigate their identities. This study found popular cultural texts played a key role in identity construction for these women.
Keywords: feminism; sexuality; submission; identity; public pedagogy